(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This report provides a thorough literature analysis on the topic of digital literacy and its impact on improving technical learning outcomes for adult learners enrolled in online distance education programs. This research looks specifically at programs that are quite technical in nature and finds and analyses the internal, external, and institutional problems that come from not having enough digital competences. It proves that being able to use digital tools effectively is crucial for succeeding in school and getting all of your assignments done on time, not just an extra talent. Cognitive overload, decreased engagement, increased anxiety, and a greater chance of dropping out were seen among adult learners with inadequate digital abilities. Several psychological, social, and infrastructure-related aspects are interrelated with digital literacy, as the review shows. Poor student performance is mostly attributable to obstacles including restricted access to technology, digital fear, and an absence of institutional support. According to the results, adult learners’ digital preparedness is affected by their socioeconomic status, their level of previous exposure to technology, and the availability of institutional support mechanisms. According to the data, universities that offered digital interventions including orientation sessions before classes started, help desk services, and adaptive learning materials had higher results for their students. The report proposes a range of tactics and policies that are responsive to context in order to tackle these issues. National policies should be put in place to guarantee that all students have equal access to digital learning opportunities, and these should include things like digital literacy tests, faculty training to help students from varied backgrounds, and the integration of digital literacy modules into early technical curriculum. In order to help adult learners thrive in online technical education, the article says that digital literacy must be approached holistically and inclusively.